Sin eaters : stories - Tankersley, Caleb (Fairbanks : University of Alaska Press, 2022)
"Magical, heartfelt, and funny, Sin Eaters paints a picture of religion and repression while hinting at the love and connection that come with healing. The stories in Caleb Tankersley's collection illuminate the shadowy edges of the American Midwest, featuring aspects of religion, sex and desire, monsters and magic, and humor."--
Intro -- Contents -- Swamp Creatures -- Candy Cigarettes -- He Told Me a Story -- Apparitions -- The Feed Corn Sea -- Branson -- Never Been More in Love -- Ghosts on TV -- In the Clouds -- A Cross is Also a Sword -- Trains -- Uncle Bob -- You're Beautiful -- Sin Eaters -- Acknowledgments
Description based on online resource; title from digital title page (viewed on September 20, 2022).
JSTOR
Keywords: Short stories, American -- 21st century; Nouvelles américaines -- 21e siècle.; Short Stories (single author); Electronic books; short stories; Short stories; Short stories; Nouvelles